The Impact of Performance-Based Assessment on Academic Writing Instruction - Dewi, Anita Candra; Sheik Mohamed; Kh. Atikur Rahman; Luís Miguel Oliveira de Barros Cardoso (Institut Agama Islam Negeri Parepare, 2024)
This study seeks to determine the positive impact of PBA, which synchronizes student achievement in the learning process with final grades. Performance-Based Assessment (PBA) is a pedagogical strategy used to achieve student targets in the following learning objectives, especially in Academic Writing courses that aim to make students competent novice writers. The Performance-Based Assessment teaching style allows students to write seminar-ready draft proposals at the end of the Academic Writing course. It was decided to adopt a single case study research design to get more thorough data about the respondents. This study used Performance-Based Assessment (PBA) in academic writing classes. This study shows that Performance-Based Assessment improves student learning, notably in Academic Writing, proving that PBA is a good teaching method.